Bibliotherapy in Totilawati Tjitrawasita’s Short Story Jakarta to Foster Empathy - Sherly Cahisnainy; Suyatno Suyatno; Titik Indarti (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study is motivated by the importance of fostering empathy in literature education amidst a modern social reality that tends to foster alienation and the decline of human harmony. Literature has the potential to serve as a reflective and therapeutic medium. However, its application in bibliotherapy-based learning integrated with a hermeneutic approach remains limited. This study aims to analyse the representation of empathy in the short story “Jakarta” by Totilawati Tjitrawasita and to examine its function as a bibliotherapy medium in literature education. The study engaged a qualitative approach with a hermeneutic interpretative method. Textual data were analysed through critical reading and interpretation based on the relationship between parts and the whole text. The findings indicate that this short story contains strong cognitive and affective empathy through the relationships between characters and the inner experiences of the main characters. The findings further illustrate that the character’s alienation represents social inequality and shifting values in modern society. Furthermore, this short story fulfills the stages of bibliotherapy, namely identification, catharsis, and insight, which demonstrate the reader’s emotional and reflective engagement. The study has demonstrated that the short story “Jakarta” can be harnessed as a bibliotherapy-based learning medium to enhance empathy and social awareness.